The Role Of English Consonants In Language Development : Acquisition And Articulation - Arya Wiranda; Tiara Dwi Lestari; Yani Lubis (Jurnal Multidisiplin Dehasen (MUDE), 2023)
This article examines the crucial role of English consonants in the language development of individuals, focusing on their acquisition and articulation processes. It explores how children acquire and master consonants in the English language, highlighting the significant milestones in their articulation development. The acquisition of English consonants plays a pivotal role in the overall language development of children. It involves the gradual learning of phonetic distinctions and the ability to produce and perceive consonant sounds accurately. This article discusses the various stages of consonant acquisition, starting from early babbling to the development of a more sophisticated consonant inventory. Articulation, the physical production of speech sounds, is a key component of consonant acquisition. The article emphasizes the importance of clear articulation for effective communication. It delves into the challenges that learners may encounter during the articulation process, such as difficulty in producing specific consonant sounds or mastering complex sound combinations. Furthermore, the article highlights the connection between consonant acquisition and vocabulary development. Adequate mastery of consonants enables learners to pronounce words correctly, enhancing their overall language proficiency and communication skills. Understanding the role of English consonants in language development is crucial for educators, parents, and speech-language pathologists. By gaining insights into the acquisition and articulation of consonant sounds, stakeholders can provide appropriate guidance and support to facilitate language learning and address any potential difficulties that learners may encounter. Overall, this article emphasizes the significance of English consonants in language development, emphasizing their role in acquisition, articulation, and vocabulary expansion.